2022
DOI: 10.3390/su142416874
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dynamics of Chlorophyll-a Concentration and Its Response to Human and Natural Factors in Lake Taihu Based on MODIS Data

Abstract: Chlorophyll-a plays an essential biochemical role in the eutrophication process, and is widely considered an important water quality indicator for assessing human activity’s effects on aquatic ecosystems. Herein, 20 years of moderate resolution imaging spectroradiometer (MODIS) data were applied to investigate the spatiotemporal patterns and trends of chlorophyll-a concentration (Chla) in the eutrophic Lake Taihu, based on a new empirical model. The validated results suggested that our developed model presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Due to the decreasing water temperature and increasing wind speed [48], the mean Chla in Lake Taihu in 2018 significantly decreased. Influenced by the rising temperature in 2019, the mean Chla in Lake Taihu also increased [49], which is consistent with the variation trend in the frequency of algal blooms proposed by Xue (2022) [41].…”
Section: Potential Reasons For the Temporal And Spatial Distributions...supporting
confidence: 89%
“…Due to the decreasing water temperature and increasing wind speed [48], the mean Chla in Lake Taihu in 2018 significantly decreased. Influenced by the rising temperature in 2019, the mean Chla in Lake Taihu also increased [49], which is consistent with the variation trend in the frequency of algal blooms proposed by Xue (2022) [41].…”
Section: Potential Reasons For the Temporal And Spatial Distributions...supporting
confidence: 89%
“…It is evident that Chl-a concentration exhibits noticeable seasonal variations, peaking in summer (56.7 µg•L −1 ) and reaching its lowest in winter ( 43 Additionally, the fluctuation of Chl-a concentration in fish ponds is more pronounced than in natural lakes. For instance, Cao et al examined the changes of Chl-a concentration in Taihu Lake from 1984 to 2019, revealing that the summer average Chl-a concentration was the highest (24.9 ± 6.9 µg•L −1 ), while the winter average was the lowest (20.9 ± 63.6 µg•L −1 ) [16], with a difference of only 4 µg•L −1 between summer and winter. Deng et al analyzed the seasonal variations of phytoplankton in Lake Taihu over twenty years, and found that Chl-a concentration is slightly higher in summer than that in winter [46].…”
Section: Seasonal Variation In Chl-a Concentrationmentioning
confidence: 99%
“…Our results revealed significant spatiotemporal variations in Chl-a concentration in fish ponds in the GBA, including interannual, seasonal, and spatial patterns. Environmental changes [49,50], climate changes [14], and human activities [5,16,17] are the primary driving forces of these changes, with temperature potentially exerting the most significant natural influence. To delve deeper into these dynamics, we calculated the water temperature of fish ponds for four seasons from 2013 to 2022, deriving the average over the decade.…”
Section: Possible Causes Of Chl-a Changesmentioning
confidence: 99%
See 2 more Smart Citations